Hand operated can crusher / Muhammad Ammar Che Suffian and Suhadiyana Hanapi - Che Suffian, Muhammad Ammar; Hanapi, Suhadiyana (School of Mechanical Engineering, 2023)
The objective of this project was to design and fabricate a can crusher to facilitate crushing aluminium cans. The project involved the process of designing the crusher, considering forces and ergonomic factors for user convenience. Once the design was finalized, it was implemented to create the actual product, using the design as a guide. Safety considerations were also paramount in this project, ensuring the product's suitability for publication. Various methods and processes such as bending, welding, drilling, and cutting were employed. The primary aim of this project was to introduce a new concept of a can crusher that is portable and user-friendly for easy tin crushing. It can be conveniently placed next to trash bins in schools or public spaces, enabling people to utilize it. This will effectively reduce the space occupied by tins in the trash, accommodating a larger quantity of aluminium cans